A imprensa cantada de Tom Zé: entre o tropicalismo e uma linha evolutiva na MPB (1964-1999) - Nery, Emília Saraiva (2014)
It is about a study concerning the conceptual, political, aesthetic tensions and legitimations in the field of Brazilian music done from thirty-six ditties-reportages of the songwriter-reporter Tom Zé (1936). His ditties constitute the main sources of the work and they were analyzed considering, principally, the notions of evolutionary line in Brazilian, Popular Music and Tropicalism . The thesis shows the historical objectivation of the referred line, from a situation of the debates concerning the state of BPM (or, in Portuguese, MPB) in the middles of the 1960 s decade which, such historical objectivation, ever since, became a significant parameter to think and organize the history of our music in a BPM historiography. In this context, the art of Tom Zé and his partners is presented like being a quarrelsome speech which reacts and aims its insertion into an evolutionary line of BPM and into a tropicalist musical heritage. The study, in pretext of the referred debate, also reflects about the singular manner how Tom Zé explains and resignifies the supposed origins of the tropicalist movement and certain myths around this one. In order to unveil the historical process in which he is inserted, some emblematic moments of his musical trajectory are coursed, such as: formation, (dis)agreements between himself and his tropicalist colleagues, musical ostracisms and rediscovery via United States. Then, thematic specificities of tomzénian ditties are approached, such as: music, backwoods, cities and politics, as long as their sonorous singularities are detached, as the experimentalist traces from the dialogue between the songwriter and musical vanguard of the second half of the twentieth century. By the end, an essay of a new historiography of the Brazilian, Popular Music is showed from the critics to the memory constructed around the existence of the Tropicalism and the exclusion of the protest music in the Brazilian musical scenario.